Uslūb al-Hakīm in Prophetic Hadith and Its Educational Impact - Dr.Noor Ul Haq (Journal of Religion and Society, 2025)
This research explores the concept, forms, and educational effects of Usloob al-Hakeem as employed by the Prophet Muhammad (peace be upon him) in his Ahadoth. The study analyzes how this rhetorical style not only serves eloquence but also fulfills deep educational, ethical, and spiritual goals. Through qualitative and analytical methodology, the paper highlights how the Prophet's responses, often diverging from the expected answer, guided the questioner towards more beneficial knowledge or moral insight. The findings show that Usloob al-Hakeem is a highly effective teaching strategy that promotes critical thinking, emotional intelligence, and moral development. It holds valuable lessons for modern educators, especially in Islamic and traditional pedagogical contexts. Keywords: Usloob al-Hakeem, Hadith, Rhetoric, Islamic Education, Prophetic Wisdom, Teaching Methods, Moral Development, Pedagogical Strategy, Indirect Guidance, Educational Psychology.